A case of repetitive myocardial infarction with unobstructed coronaries due to Churg–Strauss syndrome. Issue 2 (24th April 2019) - Gue, Ying X; Prasad, Sanjay; Isenberg, David; Gorog, Diana A
Abstract: Background: Myocardial infarction is most commonly caused by thrombosis occurring on a background of coronary atherosclerosis, resulting in reduced coronary flow. Less often, myocardial infarction can occur in the absence of coronary disease. The pathomechanism of myocardial infarction in such patients is heterogeneous and more challenging to diagnose and treat. European Society of Cardiology published a position paper on myocardial infarction in patients with non-obstructive coronary disease, with definitions and recommendations for investigations, in what has hitherto been an under-recognized and under-investigated Cinderella-like condition. However, the importance of obtaining a diagnosis is all the more important, since one treatment approach with revascularization and antithrombotic treatment does not 'fit all'. Case summary: A 70-year-old male patient presented with chest pain at rest, associated with rise in troponin and without ECG changes. A diagnosis of non-ST elevation myocardial infarction was made. Coronary angiography showed a smooth stenosis which resolved with administration of intracoronary nitrate. A diagnosis of coronary artery spasm was made, and treatment initiated. After 18 months, the patient had recurrent chest pains at rest, unresponsive to glyceryl trinitrate (GTN). Cardiac magnetic resonance revealed extension of subendocardial infarction, without inducible ischaemia. CT coronary angiogram (CTCA) showed non-obstructive coronaries. Blood tests showed significant eosinophilia, raised troponin, and C-reactive protein (CRP) that fluctuated without correlation with symptoms or any ECG changes. A diagnosis of Churg–Strauss syndrome was made, and immunosuppression commenced. Discussion: Churg–Strauss syndrome is an autoimmune vasculitis in patients with history of atopy or late-onset asthma which when involving coronary arteries can lead to myocardial injury mimicking acute coronary syndrome (ACS). Identification is important to allow initiation of immunosuppression which can prevent development or progression.